Comparison of Tooth Paste Gel Antibacterial Activity of Ethanol Extract and Ethyl Acetate Mimosa pudicafolium Against Bacteria Streptococcus Mutans Caries Dental Disease - Susanti Erikania; Rahmawati Raising (Aloha International Journal of Health Advancement (AIJHA), 2019)
Dental caries is a disease of the oral cavity caused by bacteria Streptococcus mutans. These diseases cause cavities thus damaging tissues of the teeth. One of the plants that have antibacterial activity is Mimosa pudicaFolium, which is known as one type of weed that spreads life. Active substance, alkaloids, flavonoids, saponins, triterpenes and glycosides. Prevention and appropriate treatment can affect the rate of healing of dental caries. One of the prevention is to maintain the cleanliness of your teeth and gums using a toothpaste. The aim of this study to create a gel toothpaste from ethyl aseatat extracts and fractions of ethanol extract of the leaves as well as comparing the Mimosa pudica antibacterial activity against Streptococcus mutans. This research method made three formulations gel toothpaste with respective weight ratio of extracts and fractions are 5%, 10% and 15%. Gel toothpastes made tested antibacterial activity against Streptococcus mutans bacteria in vitro with the negative control is the solvent DMSO and a positive control ciprofloxacin 25 mg/disk. The medium used was media Muller Hinton Agar (MHA). The identification results showed that ethanol extract phytochemicals Mimosa pudica Folium contain flavonoids and tannins. While only a fraction of ethyl acetate contained flavonoids. The test results showed that the antibacterial activity of the negative control DMSO not provide a response to the bacteria Streptococcus mutans, where as the positive control ciprofloxacin give a strong response at a concentration of 25 µg / disk with a diameter of 25 mm inhibition zone. The test sample gel toothpaste from ethyl acetate fraction of ethanol extract putrimalu leaves the greatest response at 15% concentration of 150 mg/ml of 15.55 mm compared with a concentration of 5%, 10% and ethanol extract on all series of concentration. Keywords: antibacterials; Streptococcus mutants; gel toothpaste; Mimosa pudica Folium